Assessing LGBT People's Perceptions of Police Legitimacy. Issue 7 (6th June 2020) - Dario, Lisa M.; Fradella, Henry F.; Verhagen, Megan; Parry, Megan M.
ABSTRACT: Although lesbian, gay, bisexual, and transgender (LGBT) people have achieved increased acceptance and access to social institutions in recent years, they have continued to be confronted with persistent homophobic attitudes, including from U.S. law enforcement personnel. Police culture often fosters these beliefs, and consequently results in the under-policing of LGBT citizens when victimized, but over-policing in places of leisure. This relationship is exacerbated when considering the intersectional effect of gender and sexual orientation, undoubtedly impacting legitimacy perceptions due to perceived (and actual) procedural injustice. Using original data collected at an LGBT festival in Arizona ( N = 428), the current study examines the relationship between procedural justice and perceptions of police legitimacy among a historically marginalized population. Implications for theory and policy are discussed, with special attention given to contextualizing the findings within the current legitimacy crisis faced by American law enforcement.